Chronic treatment with paeonol improves endothelial function in mice through inhibition of endoplasmic reticulum stress-mediated oxidative stress - Choy, K.W.; Lau, Y.S.; Murugan, Dharmani Devi; Mustafa, Mohd Rais (Public Library of Science, 2017)
Endoplasmic reticulum (ER) stress leads to endothelial dysfunction which is commonly associated in the pathogenesis of several cardiovascular diseases. We explored the vascular protective effects of chronic treatment with paeonol (2'-hydroxy-4'-methoxyacetophenone), the major compound from the root bark of Paeonia suffruticosa on ER stress-induced endothelial dysfunction in mice. Male C57BL/6J mice were injected intraperitoneally with ER stress inducer, tunicamycin (1 mg/kg/week) for 2 weeks to induce ER stress. The animals were co-administered with or without paeonol (20 mg/kg/oral gavage), reactive oxygen species (ROS) scavenger, tempol (20 mg/kg/day) or ER stress inhibitor, tauroursodeoxycholic acid (TUDCA, 150 mg/kg/day) respectively. Blood pressure and body weight were monitored weekly and at the end of treatment, the aorta was isolated for isometric force measurement. Protein associated with ER stress (GRP78, ATF6 and p-eIF2α) and oxidative stress (NOX2 and nitrotyrosine) were evaluated using Western blotting. Nitric oxide (NO) bioavailability were determined using total nitrate/nitrite assay and western blotting (phosphorylation of eNOS protein). ROS production was assessed by en face dihydroethidium staining and lucigenin-enhanced chemiluminescence assay, respectively. Our results revealed that mice treated with tunicamycin showed an increased blood pressure, reduction in body weight and impairment of endothelium-dependent relaxations (EDRs) of aorta, which were ameliorated by co-treatment with either paeonol, TUDCA and tempol. Furthermore, paeonol reduced the ROS level in the mouse aorta and improved NO bioavailability in tunicamycin treated mice. These beneficial effects of paeonol observed were comparable to those produced by TUDCA and tempol, suggesting that the actions of paeonol may involve inhibition of ER stress-mediated oxidative stress pathway. Taken together, the present results suggest that chronic treatment with paeonol preserved endothelial function and normalized blood pressure in mice induced by tunicamycin in vivo through the inhibition of ER stress-associated ROS.